Antitumor and radiosensitizing effects of SKLB-163, a novel benzothiazole-2-thiol derivative, on nasopharyngeal carcinoma by affecting the RhoGDI/JNK-1 signaling pathway. Issue 1 (October 2018) - He, Jinlan; Cai, Lei; Chen, Ye; He, Yan; Wang, Ming; Tang, Jie; Guan, Hui; Wang, Jingjing; Peng, Xingchen
Abstract: Background and purpose: SKLB-163 is a novel benzothiazole-2-thiol derivative with antitumor activities. This study investigated the effects of SKLB-163 on nasopharyngeal carcinoma (NPC) and its mechanisms. Materials and methods: Rho GDP-dissociation inhibitor (RhoGDI) expression was examined in NPC cell lines by western blot. Effects of SKLB-163 on proliferation, migration and radiosensitivity were assessed by MTT, wound healing and colony formation assays in vitro. Anti-tumor and anti-metastatic effects, and radiosensitizing effects of SKLB-163 were evaluated in a NPC lung metastatic nude mouse model and a subcutaneous xenograft mouse model. Effects of SKLB-163 on proliferation and apoptosis were assessed by PCNA immunohistochemistry and TUNEL assay in vivo. Key molecules in RhoGDI/c-Jun N-terminal kinases-1 (JNK-1) pathway were examined by western blot. Results: RhoGDI was up-regulated in NPC cell lines. SKLB-163 inhibited proliferation and migration, and increased radiosensitivity of NPC cells. SKLB-163 inhibited tumor growth and metastases, and sensitized tumor to irradiation. The radiosensitizing effects were correlated with induction of apoptosis and suppression of proliferation. The molecular mechanism was the down-regulation of RhoGDI and activation of JNK-1 signaling, and the subsequent activation of caspase-3 and the decrease in phosphorylated AKT. Conclusions: SKLB-163 shows strong anti-tumor activities against NPC and sensitizes NPC to irradiation by affecting the RhoGDI/JNK-1 pathway.